PENGEMBANGAN KERANGKA KERJA MIGRASI SISTEM PAPERLESS OFFICE - Bambang Supradono (MEDIA ELEKTRIKA, 2010)
Occurrences Paperless Office in line with advances in information technologi. Technology allows people to obtain alternative information in the processing and reading documents by reducing the use of paper that is currently called paperless office system. This study attempts to explore the framework of the migration processing and reading documents that use paper for the use of information technology. The initial step to identify business processes that use paper. Design information technology infrastructure both in terms of hardware architecture and software. and then followed by a strategy of migration to a paperless office system (PLO) So the conversion technology acquired paper documents into digital documents and transform business processes that use a lot of paper in business processes using sofware applications.Keywords: paperless office, digital documents, sofiware applications.